75th World foundry congress: new trends in developing of foundry - Yu. A. Nikolaichik (Литьë и металлургия)
The World Foundry Congress is held every two years. It is organized by the World Foundry Organization (WFO) and its member on a rotating basis. The first World Foundry Congress was held in 1923 in France, and since then, it has become a landmark international event. For over a century, the World Foundry Congress has made a great contribution to the development and exchange of scientific achievements and innovations in the foundry industry around the world, and has also contributed to the improvement of foundry technology in different countries, which provides substantial support for the progress of human civilization.The 75th World Foundry Congress was held in Deyang, Sichuan Province, People’s Republic of China (PRC) from October 25 to 30, 2024.